Maxillary Arch Dimensions in 6-Year-Old Cleft Children in Northern Finland: A Cross-Sectional Study - Mirjami Corcoran; Saujanya Karki; Leena Ylikontiola; Riitta Lithovius; George K. Sándor; Virpi Harila (International Journal of Environmental Research and Public Health, 2021)
The aim was to cross-sectionally examine the maxillary arch dimensions in 6-year-old children with cleft lip and/or palate and to compare them with the initial cleft sizes among patients with cleft palate. The study included 89 patients with clefts treated at the Oulu University Hospital. The subjects were divided into three groups: cleft palate, cleft lip, and cleft lip and palate. Study casts were scanned, and the maxillary arch dimensions were examined using a 3D program (3Shape Orthoanalyzer, Copenhagen, Denmark). The statistical methods Student’s t-test and one-way ANOVA were used to compare the means (SD) between the groups. Spearman’s correlation coefficient was used to determine the correlation between cleft severity and maxillary dimensions. A significant difference was found between different initial cleft sizes in terms of distance between the second deciduous molar and the first incisor on the right side. The intermolar width showed a negative correlation with the initial cleft size. The dimensions were shorter for clefts affecting the palate and largest for clefts affecting only the lip. Larger clefts resulted in a shorter maxilla on the right side. Many dimensions became shorter when the initial cleft was larger. Clefts of the palate resulted in smaller maxillas.